The macroeconomic variables impact on commodity futures volatility: A study on Indian markets - Nenavath Sreenu; K. S. S. Rao; D. Kishan (Cogent Business & Management, 2021)
The research investigated the impact of macroeconomic variables on the volatility of the commodity futures market in India (together with oil futures, agricultural commodity futures and metal futures). The monetary policies, financial market information and economic environments are determined by the macroeconomic variables. The low-frequency macroeconomic variables and daily price volatility is studied in the research employed by the GARCH-MIDAS model. This model simplifies the series of volatility into long- and short-run modules, which allow for the testing of the macroeconomic variables can control the long-run variance or not. The current study reveals the effect on long-run volatility factor in the commodity market, and the majority of verified data have shown that low-frequency variables have a positive impact in the long-run variance of the commodity futures market. The outcome of the study suggested that the national and international economic variables perform a substantial part in assessing the price volatility of the commodity futures market in India.
Keywords: E44; F43; G17; Q02; 650; Macroeconomic variables; emerging markets; commodity futures; volatility; GARCH-MIDAS model